"They don't need to know that.' focus groups as a model for teacher-led research and curriculum consultation. Issue 1 (2nd January 2022) - Wire, Tracey
ABSTRACT: This paper describes a focus group approach to curriculum consultation and gathering data for the purposes of research within a primary school setting. The aim of the research was to explore teachers' and parents' attitudes towards Relationships and Sex Education for Key Stage 1 children and to examine how these align with the way children of this age (5–7 years old) construct, experience and perceive their sexuality and gender. At the same time, the focus groups served as a consultation process for the development of a KS1 RSE curriculum within the school. This approach allowed adults to discuss, develop and change their perspectives and consider their own attitudes and behaviours. It also ensured that children's prior knowledge, understanding and lived experiences were the starting point of the development of the new curriculum.